1984
DOI: 10.1016/s0735-1097(84)80344-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary hemodynamic response to cigarette smoking in patients with coronary artery disease

Abstract: The acute changes in coronary blood flow and coronary resistance that occur in response to cigarette smoking have not been accurately determined. To define the factors that affect this response, coronary sinus blood flow was measured in 16 patients (group I) with coronary artery disease and in 6 patients (group II) without angiographically detectable coronary disease. Seven patients (group IA) had severe (greater than or equal to 75%) proximal left coronary lesions and nine patients (group IB) had significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
3

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 24 publications
0
37
0
3
Order By: Relevance
“…The constituents of inhaled tobacco damage the cardiovascular system by numerous mechanisms, including endothelial dysfunction, platelet dysfunction, increased coagulation, increased heart rate, blood pressure, increased myocardial oxygen demand, and vasoconstriction 18–21 . Therefore, smoking may be expected to have multiple adverse effects in patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The constituents of inhaled tobacco damage the cardiovascular system by numerous mechanisms, including endothelial dysfunction, platelet dysfunction, increased coagulation, increased heart rate, blood pressure, increased myocardial oxygen demand, and vasoconstriction 18–21 . Therefore, smoking may be expected to have multiple adverse effects in patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, coronary artery tone appears to be sensitive and responsive to alterations in az-,8-adrenergic "balance" in some patients with atherosclerotic coronary artery disease. Cryer et al 1 have shown that the plasma concentrations of norepinephrine and epinephrine rise during cigarette smoking and that the peripheral hemodynamic effects of smoking are abolished with combinedca-and /3-adrenergic blockade. Others have shown that nonselective ,e-adrenergic blockade with propranolol augments the smoking-induced increase in peripheral vascular tone.'…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to (1) a beta-adrenoceptormediated increase in heart rate and left ventricular contractility and (2) an alpha-adrenoceptor-mediated increase in coronary vasomotor tone [25,55]. By preventing the compensatory local metabolic increase in coronary blood flow, nicotine offsets the physiological adaptation of coronary flow to an increased myocardial oxygen demand [29].…”
Section: Observations and Implications In Coronary Artery Diseasementioning
confidence: 99%